Effect of Road Construction to the Growth of Small Scale Businesses in Kauga - Flavia Lyaka Nanganda (Uganda Christian University, 2025)
This study examines the impact of road construction on the growth and sustainability of smallscale businesses in Kauga, Uganda. It investigates the dual nature of infrastructure development, highlighting both the opportunities presented by improved accessibility and the challenges encountered during construction phases. Specifically, the research aims to quantify how enhanced road infrastructure affects customer traffic, sales performance, and operational efficiency for local enterprises. Utilizing a mixed-methods approach, including quantitative surveys and qualitative case studies, the research examines several key objectives: the influence of road improvements on business, operations, the specific challenges faced during construction, and the effectiveness of communication and collaboration between local authorities and business owners. Findings reveal that while improved roads can significantly boost long-term business growth and profitability, the disruptions caused by construction often lead to temporary declines in sales and logistical difficulties. The study emphasizes the necessity for proactive engagement and planning among stakeholders to mitigate negative impacts during the construction process. It advocates for an integrated approach to infrastructure development that considers the needs and concerns of small businesses to maximize the potential benefits of road improvements. Ultimately, this research contributes to the understanding of the complex interplay between infrastructure development and local economic resilience, providing actionable insights for policymakers and business leaders in Kauga.
THESIS